Neural bases of impulse control disorders in Parkinson's disease: A systematic review and an ALE meta-analysis. (December 2019) - Santangelo, Gabriella; Raimo, Simona; Cropano, Maria; Vitale, Carmine; Barone, Paolo; Trojano, Luigi
Highlights: No structural changes in any brain region were found in patients with ICD in PD. Increased brain activity in the Ventral Striatum was associated with ICD. Increased brain activity in the Orbitofrontal Cortex was associated with ICD. Decreased brain activity in Anterior Cingulate Cortex was associated with ICD. Abstract: Impulse control disorders (ICD) occur in some patients affected by Parkinson's disease (PD). Previous studies revealed an involvement of basal ganglia in ICD, but recent morphological, molecular and functional imaging studies showed that alterations of some extrastriatal regions contribute to development of ICD in PD, with mixed results. To identify the brain regions underlying ICD in PD, a systematic review of morphometric and functional studies was performed, complemented by an ALE meta-analysis of functional studies. The review of structural studies revealed no significant changes in any cortical and subcortical region in patients with ICD. The review of functional studies revealed increased activity in the Ventral Striatum and OrbitoFrontal Cortex and decreased activity in Anterior Cingulate Cortex (ACC). Clusters of hyperactivation in ventral striatum and of hypoactivation in ACC were confirmed by ALE meta-analysis. In conclusion, the present study strongly supported that ICD in PD are related to a dysfunction of limbic divisions of the striatum and of the prefrontal cortex and provided a neurofunctional basis for devising potential therapeutic interventions.